Penerapan Konsep Sekolah Alam untuk Pembentukan Karakter dan Soft Skill pada Anak Berkebutuhan Khusus (ABK) di Jogja Green School - Widyastuti, Esa Amelia; Gita Apriliana; Fingka Wahyu Anggraini; Tantri Pramadita; Saputra; Taufik Muhtarom (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to evaluate the implementation of the nature school concept at Jogja Green School in supporting character development and soft skills in children with special needs. This study uses a qualitative approach with observation and interview methods, observing the interactions of students, teachers, and nature-based activities such as gardening and farming. The subjects of this research number 25 individuals, and the data analysis technique used is the Miles and Huberman analysis technique, with data collection techniques through interviews and observations. The results of the study showed that the activity was effective in teaching responsibility, discipline, empathy, and other social skills. In addition, nature-based learning has been shown to improve students' understanding of the subject matter in a more concrete and interactive way. Despite the challenges in adapting materials for students with diverse needs, the flexibility of learning methods at Jogja Green School provides opportunities for ABK to develop according to their abilities. This study concludes that the concept of nature schools can be an effective model in inclusive education, with a focus on character development and soft skills that are important for ABK in facing life's challenges.